Burdah Al-Bushiri Poetry Perception of Kapuas Muslim Scholars - Emawati, Emawati; Liadi, Fimeir; Salihah, Putri Rafi (KARSA Journal of Social and Islamic Culture, 2020)
This article studies the perceptions of Muslim scholars on the tradition of reading Burdah poetry by al-Bushiri. This research was conducted with intensive field work in Kapuas, Central Kalimantan. A visit to the area opened an opportunity to make involved observations, which helped to understand the daily social life among Muslim scholars and Muslim community in Kapuas. Purposive sampling technique has been used in the selection of informants and interviewed eight key informants. The results revealed that reading Burdah poetry is one of the representations of socio-cultural and traditional phenomena in Kapuas Muslim community. Most of these scholars do not practice it regularly but at certain times such as during dry season, epidemic of disease, because it is considered as tawassul repellent. The perception of Kapuas Muslim scholars on Burdah Poetry can be classified into two. First, Muslim scholars who declared Burdah poetry as a high literary work having very beautiful arrangement and meaning and there was praise to the Prophet, therefore it was in line with blessings to the Prophet. The second classification, some Muslim scholars did not align Burdah poetry with blessings to the Prophet.